Modernization and National Identity: Quantitative Insights into the Role of Islamic Education in Malaysia - Rachanda Ambya; Mohamad Erihadiana; Tedi Priatna; Tatang Muh Nasir (AL-ISHLAH: Jurnal Pendidikan, 2025)
Islamic education plays a crucial role in shaping national identity and fostering social cohesion in Malaysia. This study examines its significance in the digital era, focusing on curriculum integration and contemporary challenges. A quantitative approach was employed, with data collected from 145 respondents through surveys. Participants, selected using cluster sampling, included students, parents involved in educational policy, educators, and policymakers. Data were analyzed using one-sample t-tests and descriptive statistics. Findings indicate that Islamic education significantly contributes to moral value preservation, tolerance, and inclusivity, with mean scores exceeding 4.5. However, challenges persist in curriculum adaptation to technological advancements, teacher qualification improvements, and aligning content with societal expectations. Three key dimensions emerged: the role of Islamic education in shaping identity and cohesion, its integration with digital curricula, and public expectations regarding contemporary issues. While Islamic education supports national identity and inclusivity, addressing curriculum modernization and teacher training is essential. The findings align with Durkheim's social cohesion theory and Smith’s national identity theory, highlighting the need to balance traditional values with modern pedagogy. To enhance its impact, policymakers should revise curricula to include global issues such as sustainability and technological ethics while preserving traditional values. Strengthening teacher training and resource allocation is also crucial. Future research should incorporate mixed methods and longitudinal studies to enhance generalizability and address evolving educational challenges in a globalized context.